Differing Associations Between the Most Abundant Genera of the Fecal Microbiome and Sex, Fiber Intake Score, Stress, Stool Consistency and BMI in Healthy Young Adults. (29th May 2020) - Solch, Rebecca; Beke, Matthew; Ukhanova, Maria; Mai, Volker; Langkamp-Henken, Bobbi
Abstract: Objectives: The objective of this secondary analysis was to characterize the relationships between the most abundant genera of the fecal microbiome and sex, fiber intake scores, stress, stool consistency and body mass index (BMI) in healthy young adults using data from the 1-week baseline period of a clinical study. Methods: Data from a total of 182 participants (n = 120 female) with a mean age of 19.7 ± 0.1 y (mean ± SEM) and a healthy body mass index (BMI; 23.4 ± 0.3 kg/m 2 ) were used. Participants self-reported stool consistency (Bristol stool score) as an estimate of gastrointestinal transit time and stress (0 = no stress to 10 = extremely stressed) daily for 1 week. The Rapid Eating Assessment-short questionnaire was completed at the end of baseline to assess intake frequency of fruits, vegetables and whole grains. The food frequency scores from the 3 food categories were summed for the fiber intake score. Microbial composition was determined by 16s rRNA sequencing of 1 stool sample provided during the baseline period. The top 15 genera, identified by % abundance of OTU reads, were selected for further analysis. Relationships between each of the genera and sex, fiber intake score, stress, stool consistency and BMI were assessed using a multiple linear regression model. Results: The top 15 genera in descending % abundance were Bacteroides, Faecalibacterium, Dialister, Prevotella, Parabacteroides, Ruminococcus, Oscillospira, Sutterella, Phascolarctobacterium, Blautia, Bifidobacterium, Lachnospira, Roseburia, Eubacterium and Collinsella . The % abundance of Faecalibacterium was higher in men ( P  = 0.018) and was inversely related to intake of fiber containing foods ( P  = 0.034). Ruminococcus % abundance was inversely related to BMI ( P  = 0.020). Oscillospira % abundance was higher in women ( P  = 0.012) and decreased with increasing BMI ( P  = 0.024), stress ( P  = 0.032) and stool consistency score (i.e., looser stools; P  = 0.027). Lachnospira % abundance increased with a increasing stool consistency score ( P  = 0.029) and with decreasing intake of fiber containing foods ( P  = 0.025). Conclusions: These findings show differing associations between the most abundant genera of the fecal microbiome and sex, fiber intake score, stress, stool consistency and BMI in healthy young adults. Funding Sources: Supported by Wakunaga of America Co., Ltd.